Global Metabolic Changes by Bacillus Cyclic Lipopeptide Extracts on Stress Responses of Para Rubber Leaf - Paiboon Tunsagool; Pongsakorn Kruaweangmol; Anurag Sunpapao; Arnannit Kuyyogsuy; Janthima Jaresitthikunchai; Sittiruk Roytrakul; Wanwipa Vongsangnak (Emerging Science Journal, 2023)
Changing environmental conditions can generate abiotic stress, such as the scarcity of water and exposure to chemicals. This includes biotic stress like Phytophthora palmivora infection, which causes leaf fall disease and inhibits the growth rate of para rubber seedlings, resulting in economic loss. To prevent abiotic and biotic stresses, biocontrol agents such as cyclic lipopeptides (CLPs) from Bacillus spp. have been introduced to reduce the use of chemically synthesized fungicides and fertilizers. This study aimed to use Bacillus CLP extracts as a biological agent to stimulate the plant growth system in para rubber seedlings under stress conditions compared with the exogenous plant hormone (salicylic acid, SA). CLP extracts obtained from B. subtilis PTKU12 and exogenous SA were applied to the leaves of para rubber seedlings. The extracted metabolites from each treatment were analyzed by untargeted metabolomics for metabolite identification and metabolic networks under stress responses. In both treatments, 1,702 and 979 metabolites were detected in the positive and negative ion modes of electrospray ionization, respectively. The differential analysis revealed that the accumulation of up-regulated metabolites in the treatment of CLP extracts was higher than in the exogenous SA treatment, belonging to 56 metabolic pathways. The analysis of metabolic pathways indicated that CLP extracts employed alanine, aspartate, and glutamate metabolisms for stress responses leading to plant growth promotion. These findings revealed that the metabolic network for plant growth promotion induced by BacillusCLP extracts could be considered a protective option for para rubber plantations. Doi: 10.28991/ESJ-2023-07-03-022 Full Text: PDF